Coke and preparation method thereof, negative electrode material and lithium ion battery

By preparing the focal of specific composition and structure, and through specific preparation methods, the problem that graphite negative electrode materials in the prior art is difficult to take into account high capacity and high magnification, the preparation of graphite negative electrode materials with high graphitization and high capacity is achieved, and the performance of lithium-ion batteries is improved.

CN119307279BActive Publication Date: 2025-04-25BTR NEW MATERIAL GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411850889.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

It is difficult to prepare graphite negative electrode materials that take into account both high capacity and high magnification, and it is difficult to effectively improve material performance by regulating the structure of coke raw materials.

Method used

By preparing a specific coke, its constituent elements include carbon, hydrogen, oxygen, nitrogen and sulfur, the mass content of hydrogen element is between 3.4% and 4.51%, the mass content of oxygen element is between 0.8% and 1.8%, and the high-temperature weight loss rate is between 7.5% and 11.5%. Through specific tissue structures and reaction conditions, the coking depth and structure of the coke are regulated, and graphite negative electrode materials with high graphitization and high capacity are prepared.

Benefits of technology

The high capacity and excellent rate performance of graphite negative electrode materials are achieved, and the overall performance of lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307279B_ABST
    Figure CN119307279B_ABST
Patent Text Reader

Abstract

The present application provides a coke and a preparation method thereof, a negative electrode material and a lithium-ion battery. The coke provided in the present application has a hydrogen content of H (%), an oxygen content of O (%), a high-temperature weight loss rate of V (%) at 1200°C, and satisfies 2≤V*O / H≤6. In the present application, the content of oxygen and the content of hydrogen satisfy 2≤V*O / H≤6 with the high-temperature weight loss rate of the coke, which helps to regulate the coking depth of the coke, so that the coke can maintain good processing performance while reducing the difficulty of graphitization, so as to obtain a negative electrode material with less grain boundary defects and high capacity, which helps to improve the structural stability of the negative electrode material during high-rate charge and discharge to improve the rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials, and in particular to coke and a preparation method thereof, a negative electrode material and a lithium ion battery. Background Art

[0002] Artificial graphite is one of the mainstream negative electrode materials for lithium-ion batteries. It is prepared from coke raw materials through a series of processes such as high-temperature graphitization. The coke raw materials used mainly include needle coke, petroleum coke, asphalt coke, and isotropic coke. With the rapid development of the new energy industry, the performance required of graphite negative electrode materials is getting higher and higher, such as ultra-high capacity graphite negative electrode materials, high-capacity and high-rate graphite negative electrode materials, and ultra-long cycle graphite negative electrode materials. In the field of power batteries, high-capacity and high-rate graphite negative electrode materials are the mainstream direction in the market now, and demand is growing rapidly, and coke raw materials are a key link.

[0003] The layered structure of graphite means that lithium ions can only be embedded from the end faces of graphite and are transported and diffused inside the graphite. Generally speaking, the larger the graphite crystal size and the higher the graphitization degree, the higher the capacity. However, the larger the graphite crystal size and the higher the graphitization degree, the greater the orientation of graphite, and the longer the path of lithium ion transmission, which is not conducive to the performance of rate performance. The organizational structure of coke raw materials is the basis for the formation of graphite crystals. Controlling the organizational structure of coke largely determines the size and graphitization degree of graphite crystals. In addition, the stability of graphite structure is also an important factor affecting the performance of rate performance. Improving the stability of graphite structure requires high graphitization degree, less internal defect stress of graphite, small diffusion barrier of lithium ions, and small volume change of graphite structure. High graphitization degree can be achieved by increasing the anisotropic structure content of coke. For example, some researchers have prepared high-capacity needle coke with high streamlined structure content by blending and modulating raw oil, and its gram capacity after graphitization can be higher than 355mAh / g. Low graphite crystal size and orientation can be achieved by reducing the anisotropic structural size of coke. Some researchers have developed an isotropic coke suitable for high-rate artificial graphite, which is prepared by flash distilling low-temperature coal tar to obtain the required flash material, and then coking it under an inert atmosphere. The artificial graphite prepared can meet the 6C charging constant current ratio ≥80%, but the capacity is low, only 335~340mAh / g. Some researchers have also adjusted the microstructure of coke to make it is isotropic on a macro scale to achieve fast charging, and achieved high capacity by mixing silicon oxide or nano-silicon, but the first efficiency of the resulting negative electrode material is ≤88%. However, in the actual application process, simply regulating the size of the organizational structure of coke has limited effect on both the capacity and rate performance of the negative electrode material. Further research on the coke raw materials is needed to develop graphite negative electrode materials that can take into account both high capacity and high rate. Summary of the invention

[0004] The main purpose of the present invention is to provide a coke and a preparation method thereof, a negative electrode material and a lithium ion battery, so as to solve the problem in the prior art that coke cannot be used to prepare a negative electrode material with both high capacity and high rate.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a coke, wherein the constituent elements of the coke include carbon, hydrogen, oxygen, nitrogen and sulfur, wherein the mass content of hydrogen is H (%), the mass content of oxygen is O (%), the high-temperature weight loss rate of the coke raw material is V (%), and 2≤V*O / H≤6.

[0006] Furthermore, the coke satisfies at least one of the following characteristics:

[0007] (1) The mass content of hydrogen element H (%) is 3.4%-4.51%;

[0008] (2) The hydrogen element exists in at least one of the following forms: methyl, methylene, methine, carboxyl, and hydroxyl;

[0009] (3) The mass content of oxygen element O (%) is 0.8%-1.8%;

[0010] (4) The oxygen element exists in the form of at least one of a phenol group, an aromatic ether group, an alkyl ether group, and a carbonyl group.

[0011] Furthermore, the coke satisfies at least one of the following characteristics:

[0012] (1) The mass content of sulfur element is S (%), S (%) ≤ 4.0%;

[0013] (2) The mass content of sulfur element is S (%), S (%) ≤ 2.5%;

[0014] (3) The existence forms of sulfur include pyrite sulfur, thiophene sulfur and sulfoxide sulfur; among which, based on the total mass of sulfur element, the mass proportion of pyrite sulfur is ≤5%, the mass proportion of thiophene sulfur is 40%-80%, and the mass proportion of sulfoxide sulfur is 20%-60%;

[0015] (4) The mass content of nitrogen is N (%), N (%) ≤ 2.5%;

[0016] (5) The mass content of nitrogen is N (%), N (%) ≤ 2%;

[0017] (6) The nitrogen element exists in at least one form of pyridinic nitrogen, pyrrolic nitrogen, and graphitic nitrogen.

[0018] Furthermore, the coke satisfies at least one of the following characteristics:

[0019] (1) High temperature weight loss rate V (%) is 7.5%-11.5%;

[0020] (2) The volatile gases generated by coke at 1200°C include at least one of SO2, H2S, NO, NO2, CO, CO2, H2O and hydrocarbons;

[0021] (3) The constituent elements of coke also include ash elements, and the ash elements include at least one of iron, nickel, aluminum, calcium, vanadium, cobalt, zinc, manganese, sodium, potassium, copper, chromium, magnesium and silicon;

[0022] (4) The constituent elements of coke also include ash elements, which include at least one of iron, nickel, aluminum, calcium, vanadium, cobalt, zinc, manganese, sodium, potassium, copper, chromium, magnesium and silicon, and the content of each ash element is ≤200 ppm, and the total mass content of ash elements is ≤0.6%.

[0023] Furthermore, the organizational structure of the coke raw material includes an isotropic structure, an uncoked structure, a mosaic structure, a streamlined structure and a lamellar structure, and the organizational structure of the coke satisfies at least one of the following characteristics:

[0024] (1) The volume proportion of the lamellar structure is P (%), and the volume proportion of the streamlined structure is M (%), where 80%≤P+M≤95%, and 1≤M / P≤2;

[0025] (2) The volume proportion of the lamellar structure is P (%), and P (%) is 20%-50%;

[0026] (3) The volume proportion of the lamellar structure is P (%), and P (%) is 30%-40%;

[0027] (4) The volume proportion of the streamlined structure is M (%), and M (%) is 30%-80%;

[0028] (5) The volume proportion of the streamlined structure is M (%), and M (%) is 45%-70%;

[0029] (6) The volume proportion of isotropic structure is ≤10%;

[0030] (7) The volume proportion of isotropic structure is ≤5%;

[0031] (8) The volume proportion of uncoked structure is ≤5%;

[0032] (9) The volume proportion of uncoked structure is ≤3%;

[0033] (10) The volume proportion of the mosaic structure is ≤10%;

[0034] (11) The volume proportion of the mosaic structure is ≤5%.

[0035] Furthermore, the coke satisfies at least one of the following characteristics:

[0036] (1) The true density of coke is 1.36-1.43 g / cm 3 ;

[0037] (2) The true density of coke is 1.39-1.42 g / cm 3 .

[0038] (3) The surface and interior of the coke raw material are porous, and the shape of the pores includes at least one of irregular circles, ellipses and elongated strips;

[0039] (4) The fracture surface after coke breaking is sharp or irregular;

[0040] (5) The cross section of the coke is full of holes and produces fluorescence under ultraviolet light.

[0041] In order to achieve the above object, according to another aspect of the present invention, the above preparation method is also provided, comprising the following steps:

[0042] Step S1, mixing graphene oxide and concentrated sulfuric acid for activation to obtain an activated graphene oxide material;

[0043] Step S2, nano-processing the activated graphene oxide material to obtain a graphene oxide nanomaterial;

[0044] Step S3, mixing the graphene oxide nanomaterial, the feedstock oil A and the feedstock oil B by ultrasonic stirring at 150-300° C. to obtain coking feedstock oil;

[0045] Step S4, subjecting the coking feedstock oil to a coking reaction to obtain coke;

[0046] The feedstock oil A includes the heavy oil remaining after the light oil products are extracted from the crude oil through a distillation process, and the heavy oil includes at least one of atmospheric residue oil, vacuum residue oil, and heavy asphalt;

[0047] The feedstock oil B includes high aromatic content oil obtained by fine processing of atmospheric and vacuum residue oil or heavy asphalt, and the high aromatic content oil includes at least one of desolidified oil slurry, cracking tar, thermal cracking residue oil, and catalytic oil slurry.

[0048] Furthermore, the preparation method satisfies at least one of the following characteristics:

[0049] (1) The mass ratio of feedstock oil A to feedstock oil B is 95-50:5-50;

[0050] (2) The mass ratio of the total mass of the feedstock oil A and the feedstock oil B to the mass ratio of the graphene oxide nanomaterial is 100:1-3;

[0051] (3) The mass content of asphaltene in feedstock oil A is ≤3%;

[0052] (4) The mass content of gum in the raw material oil A is 20%-50%;

[0053] (5) The mass content of aromatic components in feedstock oil A is 20%-50%;

[0054] (6) The mass content of saturated fractions in feedstock oil A is 10%-40%;

[0055] (7) The density of crude oil A at 20°C is 1 g / cm 3 -1.05 g / cm 3 ;

[0056] (8) The sulfur content of crude oil A is 1.5%-2.3% by mass;

[0057] (9) The mass content of asphaltene in feedstock oil B is ≤1.5%;

[0058] (10) The mass content of gum in feedstock oil B is ≤15%;

[0059] (11) The mass content of aromatic components in feedstock oil B is ≥ 70%;

[0060] (12) The mass content of saturated components in feedstock oil B is ≤15%;

[0061] (13) The mass content of sulfur in the feedstock oil B is 0.5%-1.5%;

[0062] (14) The density of the raw material B at 20°C is 1.08-1.2 g / cm 3 ;

[0063] (15) The coking reaction is carried out under the protection of inert gas at a pressure of 0.1-0.3 MPa;

[0064] (16) Step S4 comprises: in the first stage, the temperature of the mixed oil is raised from room temperature to 260-300°C at a controlled heating rate of 5-10°C / min, and the temperature is kept constant for 30-60s; in the second stage, the temperature is raised to 380-420°C at a controlled heating rate of 1-3°C / min, and the temperature is kept constant for 10-60s; in the third stage, the temperature is raised to 490-510°C at a controlled heating rate of 3-7°C / min, and the coking reaction is carried out, and the temperature is kept constant for 1-24h before cooling to obtain coke.

[0065] According to a third aspect of the present invention, there is provided a negative electrode material, the negative electrode material comprising graphite, which satisfies at least one of the following characteristics:

[0066] (1) The raw material of the negative electrode material contains the coke provided in the first aspect above;

[0067] (2) A method for preparing a negative electrode material comprises: subjecting the coke provided in the first aspect to carbonization treatment and graphitization treatment in sequence to obtain a negative electrode material.

[0068] According to a fourth aspect of the present invention, a lithium-ion battery is further provided. The lithium-ion battery comprises a negative electrode material, and the negative electrode material is the negative electrode material provided by the third aspect above.

[0069] By applying the technical solution of the present application, in the present application, the mass content of hydrogen element H (%), the mass content of oxygen element O (%) and the high-temperature weight loss rate V (%) of the coke raw material satisfy 2≤V*O / H≤6, which helps to regulate the coking depth of the coke, so that the coke can maintain good processing performance while reducing the difficulty of graphitization, so as to obtain a negative electrode material with fewer grain boundary defects and high capacity, which in turn helps to improve the structural stability of the negative electrode material during high-rate charge and discharge to improve the rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0070] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0071] Figure 1 A schematic diagram of the polarized organizational structure of the coke raw material of the negative electrode material provided according to Example 2 of the present invention is shown. DETAILED DESCRIPTION

[0072] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0073] As analyzed in the background technology of this application, the existing coke can increase the degree of graphitization by increasing the anisotropic structure content, reduce the graphite crystal size and orientation by reducing the anisotropic structure size, and achieve high capacity by mixing silicon oxide or nano-silicon. However, in the application process, it is difficult to develop a graphite material with both high capacity and high rate by simply regulating the size of the coke structure. In order to solve this problem, the present application provides a coke and a preparation method thereof, a graphite negative electrode material and a lithium-ion battery.

[0074] In a first typical embodiment of the present application, a coke is provided, which includes carbon, hydrogen, oxygen, nitrogen and sulfur, wherein the mass content of hydrogen is H (%), the mass content of oxygen is O (%), the high temperature weight loss rate of the coke is V (%), and 2≤V*O / H≤6.

[0075] In the present application, the high-temperature weight loss rate of coke refers to the weight loss rate V (%) of the material after the coke is heated to 1200°C at 10°C / min under nitrogen or inert atmosphere conditions and the volatile gas is discharged after the heating is completed.

[0076] In the present application, the mass content of hydrogen element H (%), the mass content of oxygen element O (%) and the high-temperature weight loss rate of the coke raw material V (%) satisfy 2≤V*O / H≤6, which helps to regulate the coking depth of the coke, so that the coke can maintain good processing performance while reducing the difficulty of graphitization, so as to obtain a graphite negative electrode material with fewer grain boundary defects and high capacity, which helps to stabilize the structure of the graphite negative electrode material during high-rate charge and discharge to improve the stone rate performance.

[0077] When V*O / H is less than 2, it indicates that the graphitization degree of the coke is low, the functional groups, side chains and side groups contained in the coke are few, the mass content of hydrogen H (%) and the mass content of oxygen O (%) are too low, the high-temperature weight loss rate of the coke V (%) is also low, and less gas is generated during the graphitization process, which is not conducive to the orderly rearrangement of the carbon layer during the graphitization process, resulting in low graphitization degree, few lithium insertion sites and low capacity of the prepared negative electrode material.

[0078] When V*O / H>6, it indicates that the graphitization degree of the coke is low, and the coke contains many functional groups, side chains, and side groups, especially a high content of fatty chains with functional groups. The presence of these group side chains will hinder the graphitization process, hinder the growth and orderly arrangement of the carbon layer, and make the obtained negative electrode material have low graphitization degree, many defects, and reduced lithium storage sites, resulting in low capacity after graphitization and low rate performance.

[0079] Typically but not limiting, in the present application, V*O / H is 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6 or a range consisting of any two of these values ​​or other values ​​within the range.

[0080] In some embodiments, controlling the mass content of hydrogen H (%) in coke to 3.4%-4.51% is more helpful in regulating the coking depth of the coke raw material, thereby reducing the difficulty of graphitization of the coke raw material and obtaining a graphite negative electrode material with high graphitization degree and high capacity.

[0081] In some embodiments, the hydrogen element mainly exists in the form of functional groups, side chain groups, etc., and its existence form can be one or more combinations of methyl (-CH3), methylene (-CH2), methyne (-CH), carboxyl (-COOH), hydroxyl (-OH), etc., so as to facilitate the production of more hydrogen-containing gas during the coking process, promote the orderly rearrangement of the carbon layer during the graphitization process, increase the degree of graphitization, and thereby improve the capacity and rate performance of the prepared graphite negative electrode material.

[0082] In some embodiments, controlling the oxygen mass content O (%) of coke to 0.8-1.8% is more conducive to adjusting the coking depth of the coke raw material, and further more conducive to obtaining a graphite negative electrode material with a high degree of graphitization and a high capacity.

[0083] In some embodiments, the oxygen element may exist in the form of one or more combinations of phenolic groups (CO), aromatic ether groups (Ar-CO), alkyl ethers (-COC-), carboxyl groups (C=O), etc., so as to generate more carbon-containing gas during the coking process, promote the orderly rearrangement of the carbon layer during the graphitization process, increase the degree of graphitization, and thereby improve the capacity and rate performance of the prepared graphite negative electrode material.

[0084] In some embodiments, the controlled sulfur content S (%) ≤ 4.0% is conducive to controlling the volatilization and emission of SO2 during the graphitization process, thereby improving the order of the graphite negative electrode material formed. In particular, when S (%) ≤ 2.5%, it is more conducive to improving the order of the graphite negative electrode material formed.

[0085] The sulfur content was tested using the German Eltra CS-i carbon-sulfur analyzer.

[0086] In some embodiments, the sulfur element exists mainly in the form of pyrite sulfur, thiophene sulfur and sulfoxide sulfur; based on the total mass of the sulfur element, the proportion of pyrite sulfur is ≤5%, the proportion of thiophene sulfur is 40%-80%, and the proportion of sulfoxide sulfur is 20%-60%, so as to generate more sulfur-containing gas during the coking process, promote the orderly rearrangement of carbon layers during graphitization, increase the degree of graphitization, and thereby improve the capacity and rate performance of the prepared graphite negative electrode material.

[0087] The sulfur-containing groups are tested using a Thermo Fisher K-Alpha X-ray photoelectron spectrometer, and other types of X-ray photoelectron spectrometers may also be used, which is not limited here.

[0088] In some embodiments, the nitrogen mass content N (%) of the coke is controlled to be ≤2.5%, so as to control the volatilization emission of NO and NO2 during the graphitization process, thereby increasing its coking depth, which is more conducive to obtaining a graphite negative electrode material with a high degree of graphitization, especially when N≤2.0%, which is more conducive to obtaining a high-capacity graphite negative electrode material.

[0089] In some embodiments, the nitrogen element may exist in the form of one or a combination of pyridinic nitrogen, pyrrolic nitrogen, and graphitic nitrogen, so as to generate more nitrogen-containing gas during the coking process, promote the orderly rearrangement of the carbon layer during the graphitization process, increase the degree of graphitization, and thereby improve the capacity and rate performance of the prepared graphite negative electrode material.

[0090] In some embodiments, the high temperature weight loss rate V (%) is 7.5-11.5%. The volatile gas generated by the coke provided in the present application at high temperature (1200°C) mainly includes a mixed gas formed by one or more gases selected from SO2, H2S, NO, NO2, CO, CO2, H2O, hydrocarbons, etc.

[0091] Typically but not limiting, the mass content H (%) of hydrogen in coke is 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, 4.51% or a range consisting of any two values ​​or other values ​​within the range; the mass content O (%) of oxygen is 0.8%, 1.0%, 1.2%, 1.5%, 1.8% or a range consisting of any two values ​​or other values ​​within the range; the high temperature weight loss rate V (%) is 7.5%, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5% or a range consisting of any two values ​​or other values ​​within the range.

[0092] In the present application, the mass content of hydrogen element H (%), the mass content of oxygen element O (%), and the mass content of nitrogen element N (%) are all tested using the German Eltra ONH-2000 oxygen, nitrogen and hydrogen analyzer.

[0093] The hydrogen-containing groups are tested using a WQF-530 Fourier transform infrared spectrometer, and other models of Fourier transform infrared spectrometers may also be used, which is not limited here.

[0094] The oxygen-containing groups and nitrogen-containing groups are tested using a Thermo Fisher K-Alpha X-ray photoelectron spectrometer. Other types of X-ray photoelectron spectrometers may also be used and are not limited here.

[0095] The high-temperature weight loss rate V (%) test was carried out using Hitachi synchronous thermogravimetric analyzer STA3000. The test conditions were heating to 1200°C at 10°C / min under nitrogen or inert atmosphere conditions. After the heating was completed, the weight loss rate V (%) of the material was calculated.

[0096] In some embodiments, the coke also includes ash elements, including one or more ash elements such as iron, nickel, aluminum, calcium, vanadium, cobalt, zinc, manganese, sodium, potassium, copper, chromium, magnesium, and silicon. The total mass content of ash is ≤0.6%, and the content of each single ash element is preferably ≤200ppm.

[0097] The above ash element content is tested using a PerkinElmer ICP 2100 inductively coupled plasma optical emission spectrometer. Other types of inductively coupled plasma optical emission spectrometers may also be used, which is not limited here.

[0098] In some embodiments, the organizational structure of the coke includes a streamlined structure, a lamellar structure, an isotropic structure, an uncoked structure, and a mosaic structure.

[0099] In some specific embodiments, the volume proportion of the sheet structure is P (%), the volume proportion of the streamlined structure is M (%), 80%≤P+M≤95%, and 1≤M / P≤2.

[0100] The streamlined structure in the organizational structure of coke is more conducive to obtaining a graphite structure with high graphitization and high order, which is beneficial to capacity. However, because during the battery charging and discharging process, lithium ions mainly enter the graphite from the end face, too high order will lead to a long transmission distance of lithium ions, and lithium ions are prone to aggregation or lithium deposition at the end face, thereby hindering the transmission of lithium ions. In addition, too high order will lead to excessive expansion of graphite, which is not conducive to the stability of the graphite structure. The order of the sheet structure is lower than that of the streamlined structure, and it is more helpful to combine it with the streamlined structure to take into account the capacity and rate performance of the graphite negative electrode material.

[0101] The organizational structure of the above-mentioned coke was tested using Carl Zeiss's Axio Scope A1 polarizing microscope. The quantitative analysis of the polarized structure was performed under a 20X objective lens. The polarizer was fixed on an automatic displacement platform, and the distance of the forward, backward, left and right movements was set. The distance between the forward, backward, left and right movements of the two movements was 200μm. During the test, the automatic displacement platform automatically moved the position of the polarizer in the set order. Each time it moved to a position, the organizational structure characteristics under the cursor were observed. The types and quantities of polarized organizational structures at a total of 300 positions were counted to calculate the volume content of each organizational structure. Among them, the definition of polarized organizational structure was carried out in accordance with the industry standard "YB / T 077-2017 Determination Method of Optical Organization of Coke". The lamellar structure refers to the organization with a length and width of the isochromatic area under the objective lens of about ≥10μm, and red, yellow and green will appear alternately when the stage is rotated. The size of the isochromatic zone under the microscope of the streamlined structure is less than 10μm in width and ≥10μm in length. It looks like a tissue flowing in one direction or arranged in parallel in bundles. Red, yellow and green colors appear alternately when the stage is rotated.

[0102] Typically but not limiting, in the present application, P+M is 80%, 82%, 85%, 88%, 90%, 92%, 95% or a range consisting of any two values ​​or other values ​​within the range; M / P is 1, 1.1, 1.2, 1.5, 1.6, 1.8, 2 or a range consisting of any two values ​​or other values ​​within the range.

[0103] In some specific embodiments, in the organizational structure of coke, the volume proportion P (%) of the flake structure is 20%-50%, and the volume proportion M (%) of the streamlined structure is 30%-80%, which is more conducive to the preparation of graphite negative electrode materials with both high capacity and excellent rate performance, especially when the volume proportion P (%) of the flake structure is 30%-45%, and the volume proportion M of the streamlined structure is 45%-70%, which is more conducive to the preparation of graphite negative electrode materials with higher capacity and better rate performance.

[0104] Typically but not limiting, in the organizational structure of coke, the volume proportion P of the lamellar structure is 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two values ​​or other values ​​within the range; the volume proportion M of the streamlined structure is 30%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or a range consisting of any two values ​​or other values ​​within the range.

[0105] In some specific embodiments, in the organizational structure of coke, the volume proportion of the isotropic structure is ≤10%, preferably ≤5%, so as to further improve the capacity and rate performance of the graphite negative electrode material prepared from coke.

[0106] In some specific embodiments, in the organizational structure of coke, the volume proportion of the uncoked structure is ≤5%, preferably ≤3%, so as to further improve the capacity and rate performance of the graphite negative electrode material prepared from coke.

[0107] In some specific embodiments, in the organizational structure of coke, the volume of the mosaic structure is ≤10%, preferably ≤5%, so as to further improve the capacity and rate performance of the graphite negative electrode material prepared from coke.

[0108] In some embodiments, the true density of the coke is 1.36-1.43 g / cm 3 , which helps to prepare graphite anode materials with high capacity, especially when the true density of the coke is 1.39-1.42 g / cm 3 When the above method is used, it is more conducive to the preparation of graphite negative electrode materials with high graphitization and high capacity.

[0109] True density refers to the ratio of the mass of a substance to its true volume under specified conditions. True density is an inherent physical property of an object. It reflects the compactness of a substance and has nothing to do with the shape, size and state of the object.

[0110] The true density of the above coke is tested using a 3H-2000TD true density meter.

[0111] Typically, but not limiting, the true density of coke is 1.36 g / cm 3, 1.37g / cm 3 , 1.38g / cm 3 , 1.39 g / cm 3 , 1.40g / cm 3 , 1.41g / cm 3 , 1.42g / cm 3 , 1.43g / cm 3 Or a range of any two values ​​or other values ​​within the range.

[0112] In some embodiments, the surface and interior of the coke are porous, and the shapes of the holes include any one or more combinations of irregular circles, ellipses, and elongated strips.

[0113] In some embodiments, the coke is broken into pieces with sharp or irregular fracture surfaces.

[0114] In some embodiments, the cross section of the coke is full of holes, and irradiating the cross section surface of the coke with an ultraviolet flashlight will produce fluorescence.

[0115] In a second typical embodiment of the present application, a method for preparing the coke of the above-mentioned graphite negative electrode material is also provided, and the preparation method comprises the following steps: step S1, mixing graphene oxide and concentrated sulfuric acid for activation to obtain an activated graphene oxide material; step S2, nano-processing the activated graphene oxide material to obtain a graphene oxide nanomaterial; step S3, mixing the graphene oxide nanomaterial, feedstock oil A and feedstock oil B at 150-300°C by ultrasonic stirring to obtain a mixed oil; step S4, coking the mixed oil to obtain a coke raw material for the graphite negative electrode material; wherein the feedstock oil A comprises the heavy oil remaining after the light oil product is extracted from the crude oil through a distillation process, and the heavy oil comprises any one of atmospheric residue oil, vacuum residue oil, and heavy asphalt, or a mixture of two or more thereof; the feedstock oil B comprises a high aromatic content oil obtained by fine processing of atmospheric and vacuum residue oil or heavy asphalt, and the high aromatic content oil comprises any one of desolidified oil slurry, cracking tar, thermal cracking residue oil, and catalytic oil slurry, or a mixture of two or more thereof.

[0116] The preparation method of the coke raw material of the graphite negative electrode material provided in the present application is to mix the graphene oxide nanomaterial, the raw oil A and the raw oil B evenly by heating and ultrasonic stirring to obtain the coking raw oil with moderate reactivity. During the coking reaction, the highly active graphene oxide nanomaterial is used to promote the uniform and rapid growth of the intermediate phase, which is helpful to generate a good intermediate phase structure but reduce the growth of the structure with too large structure size and too high orientation, so as to regulate the content and size of the structure, and obtain coke with moderate hydrogen mass content H (%), oxygen mass content O (%) and high temperature weight loss rate V (%), and 2≤V*O / H≤6, thereby meeting the demand for high-capacity and high-rate graphite negative electrode materials.

[0117] In some embodiments, in the above step S1, graphene oxide prepared by the Hummer method and concentrated sulfuric acid (purity ≥ 98%) are mixed in a mass ratio of 1:2-10, and activated under heating conditions of 60-120° C. for 1-5 hours to obtain an activated graphene oxide material.

[0118] The mass ratio of the above-mentioned graphene oxide and concentrated sulfuric acid can be 1:2, 1:4, 1:6, 1:8, 1:10 or a range value consisting of any two values ​​or other values ​​within the range. It can be understood that the greater the amount of concentrated sulfuric acid added, the higher the degree of activation of the graphene oxide, the more oxygen-containing functional groups and defects introduced, the more active sites, and the regulation of the degree of activation of the graphene oxide in conjunction with the subsequent raw oil properties and coking reaction is helpful to obtain a coke raw material that satisfies 80%≤P+M≤95% and 1≤M / P≤2.

[0119] The activation temperature may be 60° C., 70° C., 80° C., 100° C., 110° C., 120° C., or a range of any two values ​​or other values ​​within the range. It can be understood that as the temperature increases, the activation reaction is enhanced.

[0120] The activation time can be 1 h, 2 h, 3 h, 4 h, 5 h or a range value consisting of any two values ​​or other values ​​within the range. It can be understood that as the activation time increases, the activation degree of graphene oxide increases.

[0121] In some embodiments, in the above step S2, a nano-sand mill is used to perform nano-processing on the activated graphene oxide material to reduce the size to the nanoscale, thereby obtaining a graphene oxide nanomaterial.

[0122] The particle size D50 of the above-mentioned graphene oxide nanomaterial is preferably 100-800nm, so as to facilitate the preparation of a graphite negative electrode material with uniform particle size. Specifically, the graphene oxide nanomaterial D50 can be 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm ​​or a range value consisting of any two values ​​or other values ​​within the range, and the present application is not limited here.

[0123] In some embodiments, in the above step S3, the mass ratio of feedstock oil A to feedstock oil B is 95-50:5-50, specifically 95:5, 90:10, 85:15, 80:20, 75:25, 70:30, 65:35, 60:40 or a range value consisting of any two numerical values ​​or other values ​​within the range.

[0124] In some embodiments, in the above step S3, the mass ratio of the total mass of feedstock oil A and feedstock oil B to the mass ratio of graphene oxide nanomaterial is 100:1-3. Specifically, the amount of graphene oxide nanomaterial can be 1 part, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, 1.6 parts, 1.7 parts, 1.8 parts, 1.9 parts, 2 parts or a range value consisting of any two numerical values ​​or other values ​​within the range.

[0125] The component distribution of the above-mentioned coking feedstock oil can be achieved by mixing feedstock oil A and feedstock oil B in a certain proportion, or by adding aromatic compounds to the residual oil.

[0126] In some embodiments, in the above step S3, the speed of ultrasonic stirring is 50-200 r / min, the temperature of ultrasonic stirring is 150-300° C., the time of ultrasonic stirring is 0.5-3 h, and the frequency of ultrasound during ultrasonic stirring is 10-40 kHz.

[0127] The rotation speed of the ultrasonic stirring can be 50r / min, 80r / min, 100r / min, 120r / min, 150r / min, 180r / min, 200r / min or a range value consisting of any two values ​​or other values ​​within the range; the temperature of the ultrasonic stirring can be 150℃, 180℃, 200℃, 220℃, 250℃, 280℃, 300℃ or a range value consisting of any two values ​​or other values ​​within the range; the time of ultrasonic stirring can be 0.5h, 0.8h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h or a range value consisting of any two values ​​or other values ​​within the range.

[0128] In some embodiments, the mass content of asphaltene in feedstock oil A is ≤3%, specifically 1%, 1.5%, 2%, 2.5%, 3% or a range consisting of any two values ​​or other values ​​within the range.

[0129] In some embodiments, the mass content of gum in feedstock oil A is 20%-50%, specifically 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range value consisting of any two values ​​or other values ​​within the range.

[0130] In some embodiments, the mass content of the aromatic component of feedstock oil A is 20%-50%, specifically 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range value consisting of any two values ​​or other values ​​within the range.

[0131] In some embodiments, the mass content of the saturated fraction of feedstock oil A is 10%-40%, specifically 10%, 15%, 20%, 25%, 30%, 35%, 40% or a range value consisting of any two values ​​or other values ​​within the range.

[0132] In some implementations, the density of feedstock oil A (20°C) is 1-1.05 g / cm 3 , specifically 1.01 g / cm 3 , 1.015 g / cm 3 , 1.02 g / cm 3 , 1.025 g / cm 3 , 1.03 g / cm 3 , 1.035 g / cm 3 , 1.04 g / cm 3 , 1.045 g / cm 3 , 1.05 g / cm 3 Or a range of any two values ​​or other values ​​within the range.

[0133] In some embodiments, the mass content of sulfur in feedstock oil A is 1.5%-2.3%, specifically 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3% or a range value consisting of any two values ​​or other values ​​within the range.

[0134] In some embodiments, the mass content of asphaltene in feedstock oil B is ≤1.5%, specifically 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5% or a range consisting of any two values ​​or other values ​​within the range.

[0135] In some embodiments, the mass content of gum in feedstock oil B is ≤15%, specifically 5%, 7%, 9%, 11%, 13%, 15% or a range value consisting of any two values ​​or other values ​​within the range.

[0136] In some embodiments, the mass content of the aromatic components of the feedstock oil B is ≥70%, specifically 0%, 75%, 80%, 85%, 90%, 95% or a range value consisting of any two values ​​or other values ​​within the range.

[0137] In some embodiments, the mass content of the saturated fraction of the feedstock oil B is ≤15%, and can specifically be 5%, 7%, 9%, 11%, 13%, 15% or a range value consisting of any two values ​​or other values ​​within the range.

[0138] In some embodiments, the mass content of sulfur in feedstock oil B is 0.5%-1.5%, specifically 0.5%, 0.7%, 0.9%, 1.1%, 1.3%, 1.5% or a range consisting of any two values ​​or other values ​​within the range.

[0139] In some embodiments, the density (20°C) of raw material B is 1.08-1.2 g / cm 3 , specifically 1.08 g / cm 3 , 1.09 g / cm 3 , 1.1 g / cm 3 , 1.2 g / cm 3 , 1.3 g / cm 3 , 1.4 g / cm 3 , 1.5 g / cm 3 Or a range of any two values ​​or other values ​​within the range.

[0140] In some embodiments, in the above step S4, the coking reaction is carried out under the protection of inert gas, and the pressure is 0.1-0.3 MPa, such as 0.1 MPa, 0.15 MPa, 0.2 MPa, 0.25 MPa, 0.3 MPa or a range value consisting of any two values ​​or other values ​​within the range.

[0141] In some embodiments, the entire coking process is divided into three stages. Specifically, step S4 includes: in the first stage, the temperature rise rate is controlled to be 5-10°C / min to raise the temperature of the mixed oil from room temperature to 260-300°C, and the temperature is kept constant for 30-60s; in the second stage, the temperature rise rate is controlled to be 1-3°C / min to continue to rise to 380-420°C, and the temperature is kept constant for 10-60s; in the third stage, the temperature rise rate is controlled to be 3-7°C / min to continue to rise to 490-510°C for the coking reaction, and the temperature is kept constant for 1-24h before cooling and coking to obtain coke raw materials. By controlling the heating rate, constant temperature time and pressure in the three stages, it is more conducive to improving the coking degree of coke, thereby improving the capacity and rate performance of the graphite negative electrode material.

[0142] The heating rate of the first stage may be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min or a range consisting of any two values ​​or other values ​​within the range.

[0143] The temperature of the first stage may be 260° C., 270° C., 280° C., 290° C., 300° C., or a range consisting of any two values ​​or other values ​​within the range.

[0144] The constant temperature time of the first stage can be 30s, 40s, 50s, 60s, or a range value consisting of any two values ​​or other values ​​within the range.

[0145] The heating rate of the second stage can be 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min or a range consisting of any two values ​​or other values ​​within the range.

[0146] The heating rate of the third stage can be 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min or a range consisting of any two values ​​or other values ​​within the range.

[0147] The temperature for the coking reaction in the third stage is 490°C, 493°C, 495°C, 498°C, 500°C, 502°C, 505°C, 510°C or a range consisting of any two values ​​or other values ​​within the range; the insulation time for the coking reaction is 1h, 2h, 5h, 8h, 10h, 12h, 15h, 18h, 20h, 24h or a range consisting of any two values ​​or other values ​​within the range.

[0148] In a third typical embodiment of the present application, a negative electrode material is provided. The negative electrode material includes graphite, and the raw material of the negative electrode material contains the coke provided in the first typical embodiment.

[0149] Specifically, the method for preparing the negative electrode material comprises: subjecting the coke provided by the first typical embodiment to carbonization treatment and graphitization treatment in sequence to obtain the negative electrode material.

[0150] The negative electrode material provided in the present application uses coke with a moderate hydrogen mass content H (%), oxygen mass content O (%) and high-temperature weight loss rate V (%) as a raw material, and 2≤V*O / H≤6, and thus has the characteristics of few crystal defects, high capacity, high stability and high rate, and has a broader prospect in lithium-ion batteries.

[0151] In some embodiments, the temperature of the carbonization treatment is 1000-1500° C. and the time of the carbonization treatment is 10-15 hours to further improve the carbonization efficiency of the coke.

[0152] In some embodiments, the temperature of the graphitization treatment is 2800-3200° C., and the time of the graphitization treatment is 2-5 hours, so as to further improve the preparation efficiency of the graphite negative electrode material.

[0153] Specifically, the temperature of the carbonization treatment is 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, or a range value consisting of any two numerical values, or other values ​​within the range; the time of the carbonization treatment is 10h, 11h, 12h, 13h, 15h, or a range value consisting of any two numerical values, or other values ​​within the range; the temperature of the graphitization treatment is 2800°C, 2900°C, 3000°C, 3100°C, 3200°C, or a range value consisting of any two numerical values, or other values ​​within the range; the time of the graphitization treatment is 2h, 3h, 4h, 5h, or a range value consisting of any two numerical values, or other values ​​within the range.

[0154] In a fourth typical embodiment of the present application, a lithium-ion battery is provided. The lithium-ion battery includes the negative electrode material provided in the third typical embodiment, thereby having a higher capacity and excellent rate performance.

[0155] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.

[0156] It should be noted that in the following examples and comparative examples, “%” refers to “wt %”.

[0157] Example 1

[0158] This embodiment provides a coke, and a preparation method thereof comprises the following steps:

[0159] (1) Graphene oxide prepared by the Hummer method and concentrated sulfuric acid (purity ≥ 98%) were added into a round-bottom flask at a mass ratio of 1:3. The round-bottom flask was then placed in a heating reactor at 80°C for secondary deep activation for 3 h to obtain activated graphene oxide material.

[0160] (2) The activated graphene oxide material was nano-processed using an ultra-nano sand mill to reduce its size to D50 of 500±50nm, thereby obtaining graphene oxide nanomaterials.

[0161] (3) Add graphene oxide nanomaterials and raw oil A and raw oil B in a mass ratio of 1:80:20 into an ultrasonic stirring device, and perform ultrasonic stirring at 230°C, a stirring speed of 100 r / min, and an ultrasonic frequency of 20 kHz. After stirring for 1 hour, a mixed oil is obtained. The density of raw oil A is 1.01 g / cm 3 , sulfur content is 1.8%, asphaltene content is 2%, resin content is 35%, aromatic content is 30%, saturated content is 33%; the density of crude oil B is 1.1 g / cm 3, the sulfur content is 1.0%, the asphaltene content is 1%, the resin content is 6%, the aromatic content is 85%, and the saturated content is 8%.

[0162] (4) The mixed oil is added into a reactor protected by nitrogen for coking reaction. The pressure in the reactor is controlled to be 0.2 MPa. The whole coking process is carried out in three stages. In the first stage, the temperature of the mixed oil is raised from room temperature to 280°C at a controlled rate of 5°C / min and kept at a constant temperature for 45 seconds. In the second stage, the temperature is raised to 400°C at a controlled rate of 2°C / min and kept at a constant temperature for 30 seconds. In the third stage, the temperature is raised to 498°C at a controlled rate of 5°C / min and kept at a constant temperature for 12 hours. After the coking reaction is completed, the coke is cooled and taken out to obtain the coke.

[0163] Example 2

[0164] The present embodiment provides a coke, and the preparation method thereof is different from that of the embodiment 1 in that: in step (1), the mass ratio of graphene oxide and concentrated sulfuric acid (purity ≥ 98%) is 1:5, the reaction temperature is 90° C., and the reaction time is 4 h; in step (3), the mass ratio of graphene oxide nanomaterial and raw oil A and raw oil B is 1.5:70:30; in step (4), the final coking reaction temperature of the third stage is increased to 500° C., and the reaction duration is increased to 16 h.

[0165] Example 3

[0166] This embodiment provides a coke, and its preparation method is different from that of embodiment 1 in that: in step (1), the mass ratio of graphene oxide and concentrated sulfuric acid (purity ≥ 98%) is 1:5, the reaction temperature is 90° C., and the reaction time is 4 h; in step (3), the mass ratio of graphene oxide nanomaterial and raw oil A and raw oil B is 1.5:60:40; in step (4), the final coking reaction temperature of the third stage is increased to 500° C., and the reaction duration is increased to 16 h.

[0167] Example 4

[0168] The present embodiment provides a coke, and the preparation method thereof is different from that of the embodiment 1 in that: in step (1), the mass ratio of graphene oxide and concentrated sulfuric acid (purity ≥ 98%) is 1:5, the reaction temperature is 90° C., and the reaction time is 4 h; in step (3), the mass ratio of graphene oxide nanomaterial and raw oil A and raw oil B is 1.5:65:35; in step (4), the final coking reaction temperature of the third stage is increased to 500° C., and the reaction duration is increased to 20 h.

[0169] Example 5

[0170] The present embodiment provides a coke, and the preparation method thereof is different from that of the embodiment 1 in that: in step (1), the mass ratio of graphene oxide and concentrated sulfuric acid (purity ≥ 98%) is 1:10, the reaction temperature is 100° C., and the reaction time is 5 h; in step (3), the mass ratio of graphene oxide nanomaterial and raw material oil A and raw material oil B is 1.5:70:30; in step (4), the final coking reaction temperature of the third stage is increased to 500° C., and the reaction duration is increased to 20 h.

[0171] Example 6

[0172] The present embodiment provides a coke, and the preparation method thereof is different from that of the embodiment 1 in that: in step (1), the mass ratio of graphene oxide and concentrated sulfuric acid (purity ≥ 98%) is 1:10, the reaction temperature is 100° C., and the reaction time is 5 h; in step (3), the mass ratio of graphene oxide nanomaterial and raw material oil A and raw material oil B is 1.5:70:30; in step (4), the final coking reaction temperature of the third stage is increased to 490° C., and the reaction duration is increased to 20 h.

[0173] Example 7

[0174] This embodiment provides a coke, and its preparation method is different from that of embodiment 1 in that: in step (1), the mass ratio of graphene oxide and concentrated sulfuric acid (purity ≥ 98%) is 1:10, the reaction temperature is 100° C., and the reaction time is 5 h; in step (3), the mass ratio of graphene oxide nanomaterial and raw oil A and raw oil B is 2:70:30; in step (4), the final coking reaction temperature of the third stage is increased to 490° C., and the reaction duration is increased to 20 h.

[0175] Example 8

[0176] This embodiment provides a coke, and its preparation method is different from that of embodiment 1 in that: in step (1), the mass ratio of graphene oxide and concentrated sulfuric acid (purity ≥ 98%) is 1:10, the reaction temperature is 100° C., and the reaction time is 5 h; in step (3), the mass ratio of graphene oxide nanomaterial and raw oil A and raw oil B is 2:70:30; in step (4), the final coking reaction temperature of the third stage is increased to 502° C., and the reaction duration is increased to 20 h.

[0177] Example 9

[0178] This embodiment provides a coke, and its preparation method is different from that of embodiment 1 in that: in step (1), the mass ratio of graphene oxide and concentrated sulfuric acid (purity ≥ 98%) is 1:10, the reaction temperature is 110° C., and the reaction time is 5 h; in step (3), the mass ratio of graphene oxide nanomaterial and raw oil A and raw oil B is 2:65:35; in step (4), the final coking reaction temperature of the third stage is increased to 500° C., and the reaction duration is increased to 20 h.

[0179] Example 10

[0180] This embodiment provides a coke, and its preparation method is different from that of embodiment 1 in that: in step (1), the mass ratio of graphene oxide and concentrated sulfuric acid (purity ≥ 98%) is 1:8, the reaction temperature is 110° C., and the reaction time is 5 h; in step (3), the mass ratio of graphene oxide nanomaterial and raw oil A and raw oil B is 2:70:30; in step (4), the final coking reaction temperature of the third stage is increased to 500° C., and the reaction duration is increased to 16 h.

[0181] Embodiment 11

[0182] This embodiment provides a coke, and its preparation method is different from that of embodiment 1 in that: in step (1), the mass ratio of graphene oxide and concentrated sulfuric acid (purity ≥ 98%) is 1:8, the reaction temperature is 110° C., and the reaction time is 5 h; in step (3), the mass ratio of graphene oxide nanomaterial and raw oil A and raw oil B is 2:60:40; in step (4), the final coking reaction temperature of the third stage is increased to 505° C., and the reaction duration is increased to 14 h.

[0183] Example 12

[0184] This embodiment provides a coke, and its preparation method is different from that of embodiment 1 in that: in step (3), the mass ratio of graphene oxide nanomaterial, raw oil A and raw oil B is 3:60:40.

[0185] Example 13

[0186] This embodiment provides a coke, and its preparation method is different from that of embodiment 1 in that: in step (3), the mass ratio of graphene oxide nanomaterial, raw oil A and raw oil B is 1.5:95:5.

[0187] Embodiment 14

[0188] This embodiment provides a coke, and its preparation method is different from that of embodiment 1 in that: in step (3), the mass ratio of graphene oxide nanomaterial, raw oil A and raw oil B is 1.5:50:50.

[0189] Embodiment 15

[0190] The present embodiment provides a coke, and the preparation method thereof is different from that of the embodiment 1 in that: in step (4), the pressure in the reactor is controlled to be 0.1 MPa. In the first stage, the temperature of the mixed oil is raised from room temperature to 260°C at a temperature rising rate of 7°C / min, and the temperature is kept constant for 60 seconds. In the second stage, the temperature is raised to 420°C at a temperature rising rate of 3°C / min, and the temperature is kept constant for 10 seconds. In the third stage, the temperature is raised to 500°C at a temperature rising rate of 7°C / min for a coking reaction, and the duration is 12 hours. After the coking reaction is completed, the coke is cooled and the coke is taken out to obtain the coke raw material.

[0191] Example 16

[0192] The present embodiment provides a coke, and the preparation method thereof is different from that of the embodiment 1 in that: in step (4), the pressure in the reactor is controlled to be 0.3 MPa. In the first stage, the temperature of the mixed oil is raised from room temperature to 300°C at a heating rate of 3°C / min, and the temperature is kept constant for 30 seconds. In the second stage, the temperature is raised to 380°C at a heating rate of 1°C / min, and the temperature is kept constant for 60 seconds. In the third stage, the temperature is raised to 500°C at a heating rate of 3°C / min for a coking reaction, and the duration is 1 hour. After the coking reaction is completed, the coke is cooled and the coke is taken out to obtain the coke raw material.

[0193] Comparative Example 1

[0194] This comparative example provides a coke, and its preparation method is different from that of Example 1 in that in step (3), the mass ratio of graphene oxide nanomaterial, raw oil A and raw oil B is 0.5:60:40.

[0195] Comparative Example 2

[0196] This comparative example provides a coke, and its preparation method is different from that of Example 1 in that in step (3), the mass ratio of graphene oxide nanomaterial, raw oil A and raw oil B is 5:60:40.

[0197] Comparative Example 3

[0198] This comparative example provides a coke, the preparation method of which is different from that of Example 1 in that the pressure in the reactor is controlled to be 0.05 MPa in step (4).

[0199] Comparative Example 4

[0200] This comparative example provides a coke, and its preparation method is different from that of Example 1 in that the coking process in step (4) is carried out in two stages. In the first stage, the temperature of the mixed oil is raised from room temperature to 280°C at a controlled heating rate of 5°C / min, and the temperature is kept constant for 45 seconds. In the second stage, the temperature is further raised to 498°C at a controlled heating rate of 2°C / min for a coking reaction, which lasts for 12 hours. After the coking reaction is completed, the coke is cooled and the coke raw material is obtained.

[0201] Comparative Example 5

[0202] This comparative example provides a coke, and its preparation method is different from that of Example 1 in that the coking process in step (4) is carried out in two stages. In the first stage, the temperature of the mixed oil is raised from room temperature to 400°C at a controlled heating rate of 2°C / min, and the temperature is kept constant for 40s. In the second stage, the temperature is further raised to 498°C at a controlled heating rate of 5°C / min for a coking reaction, which lasts for 12h. After the coking reaction is completed, the coke is cooled and the coke raw material is obtained.

[0203] Comparative Example 6

[0204] This comparative example provides a coke, and its preparation method is different from that of Example 1 in that step (3) uses pure raw material oil B, and the final coking reaction temperature of the third stage in step (4) is increased to 495° C. to prepare the coke raw material.

[0205] Comparative Example 7

[0206] This comparative example provides a coke, and its preparation method is different from that of Example 1 in that step (3) uses pure raw material oil A, and the final coking reaction temperature of the third stage in step (4) is increased to 505° C. to prepare the coke raw material.

[0207] Comparative Example 8

[0208] This comparative example provides a coke, and its preparation method is different from that of Example 1 in that the coking process in step (4) is as follows: the temperature of the mixed oil is raised from room temperature to 500°C at a controlled heating rate of 5°C / min, and the temperature is kept constant for 12 hours.

[0209] The hydrogen content, oxygen content, volatile matter, lamellar structure content, streamlined structure content and true density of the coke provided in the above examples and comparative examples were tested, and the results are shown in Table 1 below.

[0210] The coke provided in the above embodiments and comparative examples was crushed, and the median particle size D50 of the crushed material was 11±1 μm. The crushed material was carbonized at 1150°C for 12 h, and then high-temperature graphitized at 3000°C for 3 h. The obtained material was broken up and sieved to finally obtain a graphite negative electrode material with a D50 of 11±1 μm.

[0211] The average particle size D50, gram capacity, first efficiency and rate of the above-mentioned graphite negative electrode material were tested, and the results are shown in Table 2 below.

[0212] Test Method

[0213] (1) Test method for the mass content of hydrogen H (%) and oxygen O (%) in coke:

[0214] The test was carried out using the German Eltra ONH-2000 oxygen, nitrogen and hydrogen analyzer.

[0215] (2) Test method for the mass content of sulfur element S (%) and the mass content of nitrogen element N (%) in coke:

[0216] The test was carried out using the German Eltra CS-i carbon and sulfur analyzer.

[0217] (3) Test method for total ash element content in coke:

[0218] The tests were carried out using a PerkinElmer ICP 2100 inductively coupled plasma optical emission spectrometer.

[0219] (4) Test method for high temperature weight loss rate V (%) of coke:

[0220] The test was carried out using Hitachi's STA3000 synchronous thermogravimetric analyzer. The test conditions were heating to 1200°C at 10°C / min under nitrogen or inert atmosphere conditions. After the heating was completed, the weight loss rate V (%) of the material was calculated.

[0221] (5) Test method for the volume proportion of lamellar structure and streamlined structure in the coke structure:

[0222] The organizational structure of the above-mentioned focus was tested using Carl Zeiss's Axio Scope A1 polarizing microscope. The quantitative analysis of the polarized structure was performed under a 20X objective lens. During the test, the position of the polarizer was moved sequentially, and the types and quantities of polarized organizational structures in 300 areas were randomly counted to calculate the volume proportion of the lamellar structure and the volume proportion of the streamlined structure.

[0223] (6) Test method for true density of coke:

[0224] The test was carried out using a 3H-2000T vibration density meter.

[0225] (7) Test method for median particle size D50 of graphite negative electrode material:

[0226] The particle size distribution range of the graphite negative electrode material was tested by Malvern 3000 laser particle size analyzer.

[0227] (8) Test method for the first cycle coulombic efficiency of lithium-ion button cell capacity:

[0228] The graphite negative electrode material, carboxymethyl cellulose CMC, conductive carbon black SP, and styrene-butadiene rubber SBR prepared in the examples and comparative examples were mixed uniformly in a mass ratio of 95:1.5:1.5:2. The mixed slurry was prepared into a honey paste, evenly coated on a copper foil, and vacuum dried at 130°C to obtain an electrode sheet. The electrode sheet, lithium sheet, electrolyte (1 mol / L LiPF 6EC:EMC:DMC=1:1:1) and Celgard2400 separator were assembled into a 2016-type button half-cell for the first week coulomb efficiency test.

[0229] (9) Test method for rate performance of lithium-ion button cell:

[0230] The negative electrode materials prepared in each embodiment and comparative example were used as active materials, mixed in a mass ratio of active material: conductive carbon black: CMC: SBR = 95.3:1.5:1.4:1.8, mixed with deionized water as solvent and coated on copper foil, with a coating surface density of 6.5±0.1mg / cm2, and vacuum dried at 90°C to obtain a pole piece, which was rolled to a compaction density of 1.50±0.02g / cc. The pole piece, lithium sheet, electrolyte (1mol / L LiPF6, EC:EMC:DMC=1:1:1) and Celgard 2400 separator were assembled into a 2016 type button half-cell. The button half-cell was tested for rate performance at 25±2°C, and the charge and discharge specific capacities and coulomb efficiencies of 0.1C, 0.2C, 1C and 2C were obtained. Rate test conditions: ①0.1C discharge to 0.01V, constant voltage to 0.01C, 0.1C charge to 1.5V; ②0.2C discharge to 0.01V, constant voltage to 0.01C, 0.2C charge to 1.5V; ③1C discharge to 0.01V, constant voltage to 0.01C, 0.2C charge to 1.5V; ④2C discharge to 0.01V, constant voltage to 0.01C, 0.2C charge to 1.5V. The 2C / 0.2C discharge capacity retention rate can be calculated by dividing the 2C discharge capacity by the 0.2C discharge capacity.

[0231] The above test results are shown in Table 1 and Table 2.

[0232] Table 1. Test results of coke raw materials prepared in various examples and comparative examples

[0233]

[0234] Table 2. Test results of negative electrode materials prepared in various embodiments and comparative examples

[0235]

[0236] Figure 1 The internal structure of the focus provided in Example 2 is photographed under a microscope. Figure 1It can be seen that the coke provided in Example 2 has a lamellar structure and a streamlined structure, and the two structures account for ≥80% of the organizational structure.

[0237] According to the data of Examples 1 to 4, it can be seen that the parameters of the hydrogen content, oxygen content and high temperature weight loss rate V of the coke raw material in this application are controlled to be 2≤V*O / H≤6, which maintains a suitable degree of coking, reduces the content of impurity elements, and is conducive to graphitization. At the same time, the flake structure content and streamlined structure content of the coke are controlled to be 80%≤P+M≤95% and 1≤M / P≤2, so that the negative electrode material obtained after graphitization can take into account both excellent capacity and rate performance, especially in Example 2, the capacity of the lithium battery prepared by the negative electrode material obtained therefrom reaches 355.5mAh / g, and the 2C / 0.2C capacity retention rate reaches 37.7%, which also maintains a relatively high level, and is more excellent in capacity and rate performance.

[0238] Compared with Example 1, Example 5-11 improves the degree of activation reaction of graphene oxide by adjusting the activation reaction temperature, reaction time, and the proportion of concentrated sulfuric acid. The reaction degree of graphene oxide is increased compared with Example 1. At the same time, by adjusting the raw material ratio and the coking reaction conditions, the prepared coke satisfies 2≤V*O / H≤6, and the negative electrode material formed by graphitization can still show good capacity and rate performance. However, the capacity and rate performance of Example 5-11 are lower than that of Example 1. This is because the activation degree of graphene oxide increases, the functional groups increase, the activity of coke is enhanced, more cross-linked or heterogeneous structures are formed, and the instability of the coking reaction increases, resulting in 2≤V*O / H≤6 deviating from the center value, so that the capacity and rate performance of the negative electrode material formed by coke after graphitization are reduced.

[0239] Compared with Example 1, it can be seen from Examples 15-16 that although the hydrogen content, oxygen content and high-temperature weight loss rate V of the coke have increased, they still meet the condition of 2≤V*O / H≤6. However, due to the degradation of the structure, the capacity and rate of the negative electrode material formed thereby are reduced.

[0240] Based on Examples 1-16, when the prepared coke satisfies 2≤V*O / H≤6, the capacity of the lithium battery prepared from the negative electrode material formed therefrom satisfies 347-356.9 mAh / g and the rate satisfies 29.1-37.7, while taking into account excellent capacity and rate performance.

[0241] Compared with Comparative Example 1 and Comparative Example 2, Example 1 has an amount of graphene oxide added that is too low, and an amount of graphene oxide added that is too high. As can be seen from Table 2, too low an amount of graphene oxide added will result in V*O / H ≥ 6, and too high an amount of graphene oxide added will result in V*O / H ≤ 2. This is because when the amount of graphene oxide added is too low, the coking reaction proceeds slowly, resulting in incomplete reaction and excessive residual organic components. When the amount of graphene oxide added is too high, the coking reaction is aggravated, especially the inhomogeneity of the coking reaction is aggravated, resulting in severe degradation of the structure, thereby exhibiting poor capacity and rate performance.

[0242] Compared with Example 1 and Comparative Example 3, in Example 3, the oil and gas are removed faster due to the low pressure in the kettle, but the coking time is insufficient, so that the hydrogen content is too high, resulting in V*O / H≤2, thereby showing poor capacity and rate performance.

[0243] Compared with Comparative Examples 4-5, Example 1 shows that Comparative Examples 4 and 5 use two-stage heating, wherein the heating time of Comparative Example 4 is shortened, resulting in insufficient heating of the raw oil, resulting in a low degree of coking, V*O / H ≥ 6, while the heating temperature of Comparative Example 5 in the first stage is too high, resulting in local coking, and there is a phenomenon of uneven heating of the raw materials, which leads to a high degree of local coking, V*O / H ≤ 2, and affects the growth of lamellar and streamlined structures in the organizational structure, resulting in poor capacity performance of the negative electrode material formed by coke.

[0244] In comparative example 6, the aromatic content of feedstock oil B is high, which is conducive to the formation and fusion of the intermediate phase, and finally forms more and larger streamlined structures with high order of organizational structure. However, due to the low coking temperature without the use of feedstock oil A, V*O / H=6.55>6. The larger the V*O / H value, the lower the coking degree of the coke, the higher the O content and hydrogen content contained inside, and the high O and H content indicates that the coke raw material contains more functional groups, side chains, and side groups, especially the high content of fatty chains with functional groups. The presence of these group side chains will hinder the graphitization process, hinder the growth and orderly arrangement of the carbon layer, so that the graphitization degree of the coke raw material in comparative example 6 is low, there are many defects, and the lithium storage sites are reduced, resulting in low capacity after graphitization. However, due to the high content of streamlined structure and the few lithium ion embedding paths, the favorable effects of low graphitization degree and high defect content on rate performance are weakened, resulting in poor rate performance of the negative electrode material formed after graphitization.

[0245] In comparative example 7, the feedstock A contains a high content of asphaltene and colloid that are conducive to the formation of mosaic and small-sized streamlined structures, which is conducive to the formation of large mesophase structures and thus the formation of large-sized streamlined structures. The aromatic content is low, the coking temperature is high, the reaction is violent, and because it is not combined with feedstock B, the generated large-sized streamlined structure content is small, the content of small flakes, mosaic structures and isotropic structures is high, S / P=0.9, resulting in low capacity after graphitization. In addition, V*O / H=1.362, indicating that the O and H contents are too low, which is not conducive to the orderly rearrangement of the carbon layer during the graphitization process, resulting in low graphitization degree, few lithium insertion sites, and low capacity.

[0246] Compared with Example 8, Example 1 adopts a one-stage heating method. Directly heating the temperature to the coking temperature will lead to uneven coking and low coking uniformity. The V*O / H of the obtained coke is ≥6, resulting in poor capacity and rate performance.

[0247] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A coke, characterized in that: The coke is used to prepare a graphite negative electrode material, and the coke includes carbon, hydrogen, oxygen, nitrogen and sulfur, wherein the mass content of the hydrogen is H%, the mass content of the oxygen is O%, the high temperature weight loss rate of the coke is V%, and 2≤V*O / H≤6; The mass content H% of the hydrogen element is 3.4%-4.51%; The mass content O% of the oxygen element is 0.8%-1.8%; The high temperature weight loss rate V% is 7.5%-11.5%; The high temperature weight loss rate refers to the weight loss rate (V%) of the material after the coke is heated to 1200°C at 10°C / min under nitrogen or inert atmosphere conditions and the heating is completed and the volatile gas is discharged.

2. The coke according to claim 1, characterized in that The coke satisfies at least one of the following characteristics: (1) The hydrogen element exists in at least one of methyl, methylene, methine, carboxyl and hydroxyl groups; (2) The oxygen element exists in the form of at least one of a phenolic group, an aromatic ether group, an alkyl ether group, and a carbonyl group.

3. The coke according to claim 1, characterized in that The coke satisfies at least one of the following characteristics: (1) The mass content of sulfur element is S%, S%≤4.0%; (2) The sulfur element exists in the form of pyrite sulfur, thiophenol sulfur and sulfoxide sulfur; wherein, based on the total mass of sulfur element, the mass proportion of pyrite sulfur is ≤5%, the mass proportion of thiophenol sulfur is 40%-80%, and the mass proportion of sulfoxide sulfur is 20%-60%; (3) The mass content of the nitrogen element is N%, N%≤2.5%; (4) The nitrogen element exists in at least one form of pyridinic nitrogen, pyrrolic nitrogen, and graphitic nitrogen.

4. The coke according to claim 1, characterized in that The coke satisfies at least one of the following characteristics: (1) The mass content of sulfur element is S%, S%≤2.5%; (2) The mass content of the nitrogen element is N%, N%≤2.0%.

5. The coke according to claim 1, characterized in that The coke satisfies at least one of the following characteristics: (1) The volatile gas generated by the coke at 1200° C. includes at least one of SO2, H2S, NO, NO2, CO, CO2, H2O, and hydrocarbons; (2) The constituent elements of the coke also include ash elements, and the ash elements include at least one of iron, nickel, aluminum, calcium, vanadium, cobalt, zinc, manganese, sodium, potassium, copper, chromium, magnesium, and silicon.

6. The coke according to claim 1, characterized in that The constituent elements of the coke also include ash elements, and the ash elements include at least one of iron, nickel, aluminum, calcium, vanadium, cobalt, zinc, manganese, sodium, potassium, copper, chromium, magnesium, and silicon; and the content of each of the ash elements is ≤200ppm, and the total mass content of the ash elements is ≤0.6%.

7. The coke according to any one of claims 1 to 6, characterized in that The coke structure includes at least one of an isotropic structure, an uncoked structure, a mosaic structure, a streamlined structure and a lamellar structure, and the coke structure satisfies at least one of the following characteristics: (1) The volume proportion of the sheet structure is P%, and the volume proportion of the streamlined structure is M%, wherein 80%≤P+M≤95%, and 1≤M / P≤2; (2) The volume proportion of the sheet structure is P%, where P% is 20%-50%; (3) The volume proportion of the streamlined structure is M%, where M% is 30%-80%; (4) The volume proportion of the isotropic structure is ≤10%; (5) The volume proportion of the uncoked structure is ≤5%; (6) The volume proportion of the mosaic structure is ≤10%.

8. The coke according to claim 7, characterized in that The coke structure satisfies at least one of the following characteristics: (1) The volume proportion of the sheet structure is P%, where P% is 30%-40%; (2) The volume proportion of the streamlined structure is M%, where M% is 45%-70%; (3) The volume proportion of the isotropic structure is ≤5%; (4) The volume proportion of the uncoked structure is ≤3%; (5) The volume proportion of the mosaic structure is ≤5%.

9. The coke according to any one of claims 1 to 6, characterized in that The coke satisfies at least one of the following characteristics: (1) The true density of the coke is 1.36 g / cm 3 -1.43g / cm 3 ; (2) The surface and interior of the coke are porous, and the shape of the holes includes at least one of irregular circles, ellipses and elongated strips; (3) The coke is broken into a sharp or irregular fracture surface; (4) The cross section of the focus is full of holes and produces fluorescence under ultraviolet light.

10. The coke according to any one of claims 1 to 6, characterized in that The true density of the coke is 1.39 g / cm 3 -1.42g / cm 3 .

11. A method for preparing coke, characterized in that: The preparation method comprises the following steps: Step S1, mixing graphene oxide and concentrated sulfuric acid for activation to obtain an activated graphene oxide material; Step S2, nano-processing the activated graphene oxide material to obtain a graphene oxide nanomaterial; Step S3, mixing the graphene oxide nanomaterial, the feedstock oil A and the feedstock oil B by ultrasonic stirring at 150-300° C. to obtain coking feedstock oil; Step S4, subjecting the coking feedstock oil to a coking reaction to obtain the coke; The feedstock oil A comprises the heavy oil remaining after the light oil is extracted from the crude oil through a distillation process, and the heavy oil comprises at least one of atmospheric residue oil, vacuum residue oil and heavy asphalt; The feedstock oil B comprises high aromatic content oil obtained by fine processing of atmospheric and vacuum residue oil or heavy asphalt, and the high aromatic content oil comprises at least one of desolidified oil slurry, cracked tar, thermal cracking residue oil, and catalytic oil slurry; The coke is used to prepare a graphite negative electrode material, and the coke includes carbon, hydrogen, oxygen, nitrogen and sulfur, wherein the mass content of the hydrogen is H%, the mass content of the oxygen is O%, the high temperature weight loss rate of the coke is V%, and 2≤V*O / H≤6; The mass content H% of the hydrogen element is 3.4%-4.51%; The mass content O% of the oxygen element is 0.8%-1.8%; The high temperature weight loss rate V% is 7.5%-11.5%; The high temperature weight loss rate refers to the weight loss rate (V%) of the material after the coke is heated to 1200°C at 10°C / min under nitrogen or inert atmosphere conditions and the heating is completed and the volatile gas is discharged.

12. A method for preparing coke according to claim 11, characterized in that: The preparation method meets at least one of the following characteristics: (1) The mass ratio of the feedstock oil A to the feedstock oil B is 95-50:5-50; (2) The mass ratio of the total mass of the feedstock oil A and the feedstock oil B to the mass ratio of the graphene oxide nanomaterial is 100:1-3; (3) The mass content of asphaltene in the feedstock oil A is ≤3%; (4) The mass content of the gum in the raw oil A is 20%-50%; (5) The mass content of the aromatic components of the feedstock oil A is 20%-50%; (6) The mass content of saturated components in the feedstock oil A is 10%-40%; (7) The density of the raw oil A at 20°C is 1 g / cm 3 -1.05 g / cm 3 ; (8) The mass content of sulfur in the feedstock oil A is 1.5%-2.3%; (9) The mass content of asphaltene in the feedstock oil B is ≤1.5%; (10) The mass content of gum in the feedstock oil B is ≤15%; (11) The mass content of the aromatic components of the feedstock oil B is ≥ 70%; (12) The mass content of saturated components in the feedstock oil B is ≤15%; (13) The mass content of sulfur in the feedstock oil B is 0.5%-1.5%; (14) The density of the raw oil B at 20°C is 1.08-1.2 g / cm 3 ; (15) The coking reaction is carried out under the protection of an inert gas at a pressure of 0.1-0.3 MPa; (16) The step S4 comprises: in the first stage, the temperature of the coking raw oil is raised from room temperature to 260-300°C at a controlled heating rate of 5-10°C / min, and the temperature is kept constant for 30-60s; In the second stage, the temperature is raised to 380-420°C at a controlled rate of 1-3°C / min and kept at a constant temperature for 10-60s. In the third stage, the temperature is raised to 490-510°C at a controlled rate of 3-7°C / min for a coking reaction and cooled to obtain the coke after keeping the temperature constant for 1-24h.

13. A negative electrode material, characterized in that: The negative electrode material includes graphite, and the negative electrode material satisfies at least one of the following characteristics: (1) The raw material of the negative electrode material contains the coke according to any one of claims 1 to 10; (2) The method for preparing the negative electrode material comprises: subjecting the coke according to any one of claims 1 to 10 to a carbonization treatment and a graphitization treatment in sequence to obtain the negative electrode material.

14. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode material according to claim 13.

Citation Information

Patent Citations

  • Preparation method of high-processability and high-capacity negative electrode material precursor

    CN116004267A

  • Negative electrode material, preparation method thereof and lithium ion battery

    CN117954589A